Glut3 Addiction Is a Druggable Vulnerability for a Molecularly Defined Subpopulation of Glioblastoma - Cosset, Érika; Ilmjärv, Sten; Dutoit, Valérie; Elliott, Kathryn; von Schalscha, Tami; Camargo, Maria F; Reiss, Alexander; Moroishi, Toshiro; Seguin, Laetitia; Gomez, German; Moo, Jung-Soon; Preynat-Seauve, Olivier; et al. (Cancer cell, 2017)
While molecular subtypes of glioblastoma (GBM) are defined using gene expression and mutation profiles, we identify a unique subpopulation based on addiction to the high-affinity glucose transporter, Glut3. Although Glut3 is a known driver of a cancer stem cell phenotype, direct targeting is complicated by its expression in neurons. Using established GBM lines and patient-derived stem cells, we identify a subset of tumors within the "proneural" and "classical" subtypes that are addicted to aberrant signaling from integrin αvβ3, which activates a PAK4-YAP/TAZ signaling axis to enhance Glut3 expression. This defined subpopulation of GBM is highly sensitive to agents that disrupt this pathway, including the integrin antagonist cilengitide, providing a targeted therapeutic strategy for this unique subset of GBM tumors.